Methodological issues and practices in ethnography - Troman, Geoff, 1946-; Jeffrey, Bob, 1946-; Walford, Geoffrey (Elsevier JAI, 2005)
What counts as ethnography and what counts as good ethnography are both highly contested. This volume brings together chapters presenting a diversity of views on some of the current issues and practices in ethnographic methodology. It does not try to present a single coherent view but, through its heterogeneity, illustrates the strengths and impact of the debate. The collection includes chapters on the ethnographic research process; the use of photographic diaries; the idea of toleration in the research process; and the personal aspects of research. It has chapters that question generalisation; perceive ethnography as a potential form of surveillance; analyse the notion of display in ethnography; critique the way culture is commonly theorised; and examine the possibilities of comparative ethnographic work. It also includes and exchange of views between Martyn Hammersley and Barbara Korth on partisan research.
Some papers originally presented at an annual 2-day residential conference.
Keywords: Educational anthropology -- Methodology -- Congresses.; Ethnology -- Methodology -- Congresses.; Physical anthropology & ethnography.; Education -- Research.; elektronické knihy; electronic books